A retrospective study on the outcome of pulpotomy with iRoot BP plus in primary molars and its relationship with hemostasis time - Guangyun Lai; Kai Sheng; Jin Zhao; Ning Ding; Shimin Zhao; Jun Wang (BMC, 2024)
Abstract Background Pulpotomy is a crucial method to preserve primary teeth until natural exfoliation. This study aimed to evaluate the clinical and radiographic outcomes of pulpotomy with iRoot BP Plus in primary molars and to explore the association between hemostasis time and these outcomes. Methods Primary molars that underwent iRoot BP Plus pulpotomy and were followed for at least 12 months were selected for this study. Clinical and radiographic data were collected, and the success rate was analyzed in relation to factors such as hemostasis time, tooth type, and arch type. The tests of significance used were the chi-square test, Fisher's exact test, or Kruskal-Wallis test. Statistical significance was set at P < 0.05. Results A total of 183 teeth in 106 patients were included in the analysis. The follow-up period fell into a range of 1-3 years, with a mean of 1.6 years. The clinical and radiographic success rates were 96.7% and 92.9%, respectively. The earliest time to observe the radiographic failures was half a year after the treatment, and the latest time was two years after the treatment. Among all the teeth, 130 were recorded with hemostasis time before the application of iRoot BP Plus. Compared to teeth with a hemostasis time of 5 min or less, teeth with a hemostasis time exceeding 5 min showed no significant differences in clinical and radiographic success (P = 1.000 and 0.879). Additionally, neither arch nor teeth type showed a relationship with the pulpotomy success rate (P > 0.05). Conclusions Pulpotomy using iRoot BP Plus in primary molars achieved favorable results. The hemostasis time may not significantly impact the outcomes of pulpotomy using iRoot BP Plus in primary molars.